Sejarah dan Modus Operandi Mafia Peradilan di Indonesia - Winarta, Frans Hendra (LAW REVIEW, 2002)
Do you really care about justice in Indonesia? We have laws requiring judges and prosecutors to produce justice, but there is no enforcement to make them obey the law. Â Judicial defects and corruption that convicts innocent people instead of criminals means more criminal walking free, more crime and more risk to you and me. The same miscarriage of justice atrocities happen in civil court and it can rob you of every thing you own. Corruption is systemic when a government agency only supplies a public good or service if an otherwise unwilling transfer of wealth takes place from an individual or firm to the public sector through bribery extortion, fraud or embrezzlement. Rose-Ackerman states that "wide spread corruption is a sympton that the state is functioning, poorly" Do you agree ?Â